2014
DOI: 10.1002/chem.201303207
|View full text |Cite
|
Sign up to set email alerts
|

Plant Antimicrobial Peptides Snakin‐1 and Snakin‐2: Chemical Synthesis and Insights into the Disulfide Connectivity

Abstract: Antimicrobial peptides and proteins represent an important class of plant defensive compounds against pathogens and provide a rich source of lead compounds in the field of drug discovery. We describe the effective preparation of the cysteine-rich snakin-1 and -2 antimicrobial peptides by using a combination of solid-phase synthesis and native chemical ligation. A subsequent cysteine/cystine mediated oxidative folding to form the six internal disulfide bonds concurrently gave the folded proteins in 40-50 % yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…6, F. oxysporum was highly susceptible to recombinant SN-1 and spore germination was completely inhibited with 60 μM of SN-1. This result was in accordance with the findings described in previous reports for the potato native SN-1 and chemically synthetic SN-1 [19,24].…”
Section: Growth Inhibitory Activity Of Recombinant Sn-1 Against Filamsupporting
confidence: 94%
See 3 more Smart Citations
“…6, F. oxysporum was highly susceptible to recombinant SN-1 and spore germination was completely inhibited with 60 μM of SN-1. This result was in accordance with the findings described in previous reports for the potato native SN-1 and chemically synthetic SN-1 [19,24].…”
Section: Growth Inhibitory Activity Of Recombinant Sn-1 Against Filamsupporting
confidence: 94%
“…Numerous reports have documented the strong antimicrobial activities of snakin peptides against a wide range of microorganisms [11,19,21,24,26,27]. Enhanced resistance to pathogen infections has also been reported in plants that express snakin genes [28,29].…”
Section: Hemolytic Assays Of Recombinant Sn-1mentioning
confidence: 99%
See 2 more Smart Citations
“…37 The disulfide pattern of the synthetic Snakin-2 protein, in which 3 pairs of disulfide bonds has been determined as CysIII-CysIV, CysVIII-CysXI and CysIX-CysX, is different slightly with that of the Snakin-1 protein. 38 The previous researches have shown that cysteine disulfide bond formation mode affects the spatial protein structure and function directly. 39 Normally, GASA proteins form 5 or 6 disulfide bonds and these disulfide bonds may be necessary for the senior structural of GASA and be critical for the GASA protein interactions with other proteins.…”
Section: Structure Of Gasa Proteinsmentioning
confidence: 99%